Brand Ambassador and Customer Engagement of e-Commerce Brand TV Show: The Use of NCT U and NCT 127 for Tokopedia Campaign ‘Waktu Indonesia Belanja’ - Reza Irfan Pambudi (Jobmark: Journal of Branding and Marketing Communication, 2022)
Increasingly fierce competition forces a company or brand to make effective and creative marketing strategies by using K-pop artists as brand ambassadors. The use of K-pop artists is currently popular with e-commerce brands in Indonesia, including Tokopedia. Tokopedia uses NCT U and NCT 127 in the Tokopedia WIB (Indonesian Shopping Time) TV Show campaign to increase customer engagement. This article explains how the role of NCT U and NCT 127 as brand ambassadors in the Tokopedia WIB TV Show campaign and the relationship between brand ambassadors and customer engagement. By using an intrinsic case study with a qualitative-descriptive approach, the analysis found that the use of NCT U and NCT 127 brand ambassadors in the Tokopedia WIB TV Show campaign had a significant impact on Tokopedia, especially in increasing TPV (Total Purchase Value) and TVI (Total Value Items). However, Tokopedia's customer engagement through this brand ambassadoring strategy is effective in only three aspects: consumption, curation, and collaboration. Thus, the Tokopedia WIB TV Show campaign strategy tends to be an effort to increase awareness, reach new users, and maintain existing relationships with old users.